Odontogenic MSC Heterogeneity: Challenges and Opportunities for Regenerative Medicine - Chen, Yuan; Zhang, Zhaoyichun; Yang, Xiaoxue; Liu, Anqi; Liu, Shiyu; Feng, Jianying; Xuan, Kun (Frontiers in Physiology, 2022)
Cellular heterogeneity refers to the genetic and phenotypic differences among cells, which reflect their various fate choices, including viability, proliferation, self-renewal probability, and differentiation into different lineages. In recent years, research on the heterogeneity of mesenchymal stem cells has made some progress. Odontogenic mesenchymal stem cells share the characteristics of mesenchymal stem cells, namely, good accessibility, low immunogenicity and high stemness. In addition, they also exhibit the characteristics of vasculogenesis and neurogenesis, making them attractive for tissue engineering and regenerative medicine. However, the usage of mesenchymal stem cell subgroups differs in different diseases. Furthermore, because of the heterogeneity of odontogenic mesenchymal stem cells, their application in tissue regeneration and disease management is restricted. Findings related to the heterogeneity of odontogenic mesenchymal stem cells urgently need to be summarized, thus, we reviewed studies on odontogenic mesenchymal stem cells and their specific subpopulations, in order to provide indications for further research on the stem cell regenerative therapy.